Optimizing a day trading strategy based on support and resistance levels: ATR and LWTI contributions - Gani, Khirreddine; Chibane , Safa; Lemchenak , Chiraz Lamiss (Journal of Research in Finance and Accounting, 2025)
This article examines the effectiveness of a day trading strategy based on support and resistance levels, by assessing the contribution of technical indicators such as the Average True Range (ATR) and the Larry Williams Large Trade Index (LWTI). The study is based on a quantitative and comparative approach, applied to four major financial assets: Bitcoin, EUR/USD, gold (CFD) and the S&P 500 index (CFD), using hourly data from January 2024 to March 2025. Through a series of backtests, several configurations of the strategy are tested: the basic strategy, the integration of the ATR alone, the integration of the LWTI alone, and finally the combination of the two indicators. Performance is assessed using measures such as return, Sharpe ratio, maximum drawdown and profit factor. The results show that the addition of technical indicators significantly improves risk management and profitability, particularly when ATR and LWTI are combined. This research makes a useful empirical contribution to traders and technical analysts seeking robust strategies for day trading in volatile markets.